2018
DOI: 10.4081/aiua.2018.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in patients taking psychotropic drugs and treated with phosphodiesterase-5 inhibitors

Abstract: Objectives: The aim of this study was to assess the prevalence of patients with Erectile Dysfunction (ED) receiving psychotropic drugs, the impact of these drugs on hormonal profile, and the efficacy of PDE5-i in these patients. Materials and methods: We recruited 1872 patients referring for ED to our Andrology Unit. Assessment included serum testosterone, gonadotropins, TSH, prolactin, and PSA, and the IIEF-5 questionnaire for ED diagnosis. Inclusion criteria were age 21-75 years and IIEF-5 total score ≤ 21; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…For instance, consistent with beneficial effects of indomethacin in preclinical studies on lithium-related erectile dysfunction in rats [ 32 ], a recent clinical trial found that aspirin may improve erectile function in patients with bipolar disorders taking lithium [ 104 ]. Treatment with PDE5 inhibitors could also be another option, as they have been found to be beneficial both in antipsychotic-induced erectile dysfunction [ 105 , 106 ] as well as in subjects treated with lithium combined with other psychotherapeutic agents [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, consistent with beneficial effects of indomethacin in preclinical studies on lithium-related erectile dysfunction in rats [ 32 ], a recent clinical trial found that aspirin may improve erectile function in patients with bipolar disorders taking lithium [ 104 ]. Treatment with PDE5 inhibitors could also be another option, as they have been found to be beneficial both in antipsychotic-induced erectile dysfunction [ 105 , 106 ] as well as in subjects treated with lithium combined with other psychotherapeutic agents [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDE5 inhibitors (e.g., sildenafil) have been shown to be beneficial in the treatment of erectile dysfunction related to antipsychotics therapy [ 105 , 106 ]. More recent investigation has also demonstrated that patients treated with lithium combined with other psychotherapeutic agents had improvement in their erectile dysfunction after treatment with PDE5 inhibitors [ 107 ]. Clearly, more studies are needed to investigate several other approaches that could be beneficial in improving erectile and sexual function in patients receiving lithium.…”
Section: Lithium and Sexual Dysfunctionmentioning
confidence: 99%
“…Firstly, we found that a proportion of the participants in MMT used benzodiazepines (both self-administered and medically prescribed) during methadone treatment. This was the only admitted psychopharmacological treatment, and although its presence may interfere with the results [27] (benzodiazepines are psychotropic drugs with some adverse sexual effects) [28], it is not easy to find patients on methadone treatment in monotherapy. Secondly, another limitation of the study is bias due to its retrospective design (instead of prospective one); however, the relatively high mean duration of methadone treatment (6.34 ± 6.74 and 9.85 ± 7.78 years of treatment for men and women, respectively) avoids bias in the recalling symptoms of sexual dysfunction prior to initiating MMT, which would influence the result of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some aspects of sexual functioning, such as subjective satisfaction and sexual pain, were not evaluated, since they are not included in the PRSexDQ-SALSEX Questionnaire, but could be taken into consideration in further studies [59]. Being a naturalistic study, patients could take benzodiazepines according to usual clinical practice and these could have some effect on sexual dysfunction [60,61]; however, the doses used were low and only lasted a short time (3–6 weeks).…”
Section: Discussionmentioning
confidence: 99%